Consumer Willingness to Pay of Organic Rice and The Factors which Affected in Pontianak - Heru Setiyadi; Slamet Hartono; Dwidjono Hadi Darwanto (Jurnal Ilmu Pertanian, 2016)
Organic rice is claimed as one of staples food alternative choice. Consuming organic rice is not only about fulfilling the quality needs but also a part of life style. Organic rice is also available in many modern retails in Pontianak so that it is affordable enough to be consumed by Pontianak’s residents. The aims of study were to analyze Willingness To Pay (WTP) of consumers with Contingent Valuation Method (CVM) and find factors affected consumers WTP value of organic rice . Primary data were collected during March to April 2016 and analyzed by multiple regression. The samples of Pontianak’s residents were used as respondents. The result showed that willingness to pay rate of organic rice in Pontianak was low. The age, price of organic rice, ergonomic packaging, respondent expenditure in month, and non-organic rice price affected WTP  with marked positive, while marital status factor had negative marked.